IMAGE FORGERY DETECTION USING IMAGE PROCESSING (International Journal of Food and Nutritional Sciences, 2022)
In today’s technical world, the digital image is a vital part of many application domains. The meaning of image forgery is the manipulation of digital images to hide important information or output false information. Due to the introduction of modern image processing tools, digital image forgery is at its peak. Copy-move forgery is one of the most commonly used techniques to perform image forgery. The aim of the proposed system is to detect and highlight the malpractices performed on modern-day digital images.